Pengaruh I’rab dalam Menciptakan Ritme dan Irama dalam Surat Ar-Ra'd - Heni Verawati; Aulia Ranny Priyatna; Diah Mukminatul Hasimi (Tapis: Jurnal Penelitian Ilmiah, 2025)
This research discusses the influence of i’rab, as one aspect of Arabic grammar, in creating rhythm and melody in the recitation of Surah Ar-Ra'd. I’rab plays an important role in determining the final form of words in sentences, which not only affects the meaning but also the phonetic beauty in the recitation of the Qur'an. Surah Ar-Ra'd was chosen as the object of research because it is rich in complex language structures and varied use of i’rab, with verses full of deep meanings and natural metaphors. This research uses a qualitative method with a linguistic analysis approach, examining how changes in i’rab at the end of words in the verses of the surah affect the flow of sound and rhythm in the recitation of the Al-Qur’anul Karim. The data source used is the text of the Qur'an, specifically Surah Ar-Ra'd, which is analyzed based on the rules of i'rab and tajwid. The research results show that the consistent use of i’rab significantly contributes to the rhythmic beauty of this surah, strengthening the relationship between meaning and phonetic aesthetics in the Al-Qur'an text. I'rab, which is a grammatical marker in the Arabic language, plays a role beyond merely indicating syntactic functions. It also serves as a phonetic element that creates a beautiful melody when the verses of the Quran are recited. This research highlights the importance of understanding i’rab in appreciating the linguistic and artistic richness of the Qur'an.